Listeria monocytogenes and Staphylococcus aureus coinfection in a patient with multiple myeloma: Case report - Roberta Vaikutyte-Ramanauskiene; Danguole Vaznaisiene (Heliyon)
Introduction: Listeria monocytogenes is a formidable pathogen that poses a significant threat to immunocompromised and might cause rare atypical forms of the disease especially complicated with Staphylococcus aureus coinfection. Case: We present a case of a patient with L. monocytogenes meningoencephalitis, endocarditis, sepsis, and S. aureus osteomyelitis, highlighting the complexities of managing disseminated polymicrobial infection. A 64-year-old female with multiple myeloma treated with chemotherapy presented with fever, altered mental status, nausea, and diarrhea to the emergency department. During the physical examination, the patient was feverish, had a hemorrhagic rash and an abscess on the right thumb. Neurologically – nuchal rigidity was seen and the finger-nose test was abnormal. Blood tests and cerebrospinal fluid analysis were consistent with bacterial meningitis. The roentgenogram revealed osteomyelitis involving the right thumb. Later L. monocytogenes was identified in blood and cerebrospinal fluid cultures. The abscess was drained, and pus culture identified S. aureus. Echocardiography revealed vegetation on the aortic valve. The patient was initially treated with ceftriaxone, ampicillin, gentamicin, with clindamycin and ciprofloxacin for osteomyelitis and later with ampicillin/sulbactam and ciprofloxacin to cover both pathogens and pathologies. Due to an allergic reaction to ampicillin, treatment was changed to vancomycin. After 4 weeks of antibiotic therapy patient fully recovered and continued chemotherapy for multiple myeloma. Conclusion: In conclusion, this case emphasizes the intersection of hematological malignancy, chemotherapy-related immunosuppression, and subsequent severe disseminated bacterial infections and coinfections. Prompt diagnosis and adequate treatment of the disease and its complications is key to the successful recovery.